Bactericidal activities of teicoplanin, vancomycin, and gentamicin alone and in combination against Staphylococcus aureus in an in vitro pharmacodynamic model of endocarditis. - McGrath, B J (1994)
We adapted an in vitro pharmacodynamic model of infection to incorporate simulated endocardial vegetations. The bactericidal activities of teicoplanin, vancomycin, gentamicin, and various combinations of these drugs were studied against a strain of methicillin-susceptible Staphylococcus aureus obtained from a patient being treated for endocarditis at Detroit Receiving Hospital. Bacteria were grown overnight, concentrated, and added to a mixture of cryoprecipitate (80%) and thrombin (10%) to achieve approximately 5 x 10(9) CFU/g. Fibrin clots (8 to 10) were suspended into the model, removed at 24, 48, and 72 h in duplicate, weighed, and homogenized in 1.25% trypsin. Control experiments were conducted to characterize the growth kinetics. The following antibiotics were administered to simulate the pharmacokinetics of the drugs in humans: teicoplanin at 3 and 15 mg/kg of body weight, vancomycin at 15 mg/kg, and gentamicin at 1 mg/kg. Fibrin clot samples used to detect resistance were plated on antibiotic-containing tryptic soy agar plates. For the teicoplanin and vancomycin regimens, protein binding to cryoprecipitate, thrombin, and fibrin clot was determined to be 32, 43, and 50% and 26, 28, and 29%, respectively. In comparison with no treatment, vancomycin or teicoplanin at 15 mg/kg or either of these regimens combined with gentamicin significantly reduced bacterial counts (P < 0.0001). Monotherapy with teicoplanin at 3 mg/kg or gentamicin resulted in no killing activity. Combination treatment with teicoplanin at 3 mg/kg and gentamicin resulted in the killing of approximately 2 log10 CFU/g by 72 h and the development of resistance to gentamicin. The results obtained with the in vitro model of endocarditis are similar to the results reported by several investigators with the rabbit model of infective endocarditis. This unique infection model is useful for designing initial drug dosage regimens and may be predictive of drug efficacy against infective endocarditis.